Judicious Use of Coagulants in Primary Treatment of Combined Effluent of Starch and Liquid Glucose Industries and a Tentative Design of an Effluent Treatment Plant - Ansari, I.A.; Jalukar, R.S.; Malik, G.M. (Asian Journal of Chemistry, 2010)
A treatability study was carried out on a combined effluent of starch and liquid glucose industries using different chemicals for primary treatment so as to make the effluent more amenable to secondary treatment and subsequently reduce the energy consumption. The doses of laboratory scale investigation were implemented at plant level to assess the accuracy of test. Chemicals like alum, lime, ferric chloride and ferrous sulphate were utilized in various doses ranging from 300 mg/L to 600 mg/L. The maximum suspended solids and organic removal efficiencies were found to be 45–60% and 40–50% respectively. The object of this investigation was achieved by the successful trials of the results of treatability study at the field. A tentative flow diagram of effluent treatment plant is evolved which should serve as a guideline for designing a new plant based on this type of combined effluent. This paper also highlights the characteristics of combined effluent and detailed results of the study.